Transformational Leadership in Empowering Organizational Capacity - Muhaimin, Hikmah; Septa Wihara, Dhiyan; Hasan Afandi, Ahmad (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
Change is an unavoidable phenomenon and organizations must develop their change capacity in order to survive in competition. The purpose of this study was to examine the determinants and impacts of organizational capacity for change (OCC). In addition, the moderating influence of empowerment on transformational leadership change is also examined in influencing the organization's capacity to change and remain empowered. The hypothesis is tested using the data obtained from the survey. A total of 200 questionnaires were filled in by management as respondents and used for data analysis in this research using the survey method. The results of the study show that the orientation of transformational leadership has a positive effect on OCC. Likewise, the influence of OCC on empowerment. To increase the capacity for change, administrators at Islamic boarding schools can increase the orientation of transformational leadership so that Islamic boarding schools can increase empowerment by not changing the existing culture at Islamic boarding schools and remain empowered according to applicable regulations. This research empirically examines OCC in the context of Islamic boarding schools which are shaped by leader orientation. Furthermore, OCC has a mediating role in the influence of leadership on the empowerment of Islamic boarding schools. In addition, OCC in this study was tested with 3 dimensions (learning, process, and context) which were previously proposed only conceptually. Transformational leadership has the organizational capacity to change. In the end, this research proposes and shows that the organizational context (culture) plays an important role in the organizational capacity for change (OCC) in developing empowerment.